Sex trafficking and human rights : the status of women and state responses - Smith-Cannoy, Heather M.; Rodda, Patricia C.; Smith, Charles Anthony, 1961- (Georgetown University Press, 2022)
"Human trafficking for the sex trade is a form of modern day slavery that ensnares thousands of victims each year around the globe. Women and girls make up the majority of victims of sex trafficking, and Heather Smith-Cannoy, Patricia C. Rodda, and Charles Anthony Smith focus their analysis on the complex conditions that lead to trafficking of women and girls and the varied state responses to it. The authors analyze sex trafficking in five countries: India, Thailand, Russia, Nigeria, and Brazil. This book furthers our understanding of sex trafficking by bringing to the forefront the cultural, political, and economic status of women in society. The authors' research demonstrates that state responsiveness to human trafficking is shaped by the rights afforded to women in these societies. While combatting human trafficking is a multi-scalar problem with a host of conflating variables, a common theme in the effectiveness of state responses is the degree to which women and girls are perceived as, and actually are, full citizens. The authors demonstrate that the objectification, commodification, and structural and cultural oppression of women and girls enables states to ignore or minimally address human trafficking"--